2017
DOI: 10.1103/physrevb.95.155405
|View full text |Cite
|
Sign up to set email alerts
|

Effects of defects on thermoelectric properties of carbon nanotubes

Abstract: Carbon nanotubes (CNTs) have recently attracted attention as materials for flexible thermoelectric devices. To provide theoretical guideline of how defects influence the thermoelectric performance of CNTs, we theoretically studied the effects of defects (vacancies and Stone-Wales defects) on its thermoelectric properties; thermal conductance, electrical conductance, and Seebeck coefficient. The results revealed that the defects mostly strongly suppresses the electron conductance, and deteriorates the thermoele… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 61 publications
(89 reference statements)
1
43
1
1
Order By: Relevance
“…The inplane thermal conductivity of SWNT sheets varied within two orders of magnitude in the literatures as summarized in Table S3. Therefore, the difference of the thermal conductivity range between our results (9.16-17.9 W m −1 K −1 ) and reported values (80-370 W m −1 K −1 ) was probably due to the difference of either SWNT diameter [53], length [54,55], bundle size [56], anisotropy [57,58], defect density [43], mass density [59] of SWNTs or measurement accuracy [42,[60][61][62]. We also recognized that the s-SWNT sheets had lower thermal conductivity than that of the unsorted SWNT sheet.…”
Section: Te Properties Of S-swnt Sheetscontrasting
confidence: 66%
See 2 more Smart Citations
“…The inplane thermal conductivity of SWNT sheets varied within two orders of magnitude in the literatures as summarized in Table S3. Therefore, the difference of the thermal conductivity range between our results (9.16-17.9 W m −1 K −1 ) and reported values (80-370 W m −1 K −1 ) was probably due to the difference of either SWNT diameter [53], length [54,55], bundle size [56], anisotropy [57,58], defect density [43], mass density [59] of SWNTs or measurement accuracy [42,[60][61][62]. We also recognized that the s-SWNT sheets had lower thermal conductivity than that of the unsorted SWNT sheet.…”
Section: Te Properties Of S-swnt Sheetscontrasting
confidence: 66%
“…We assumed that an introduction of defects and shortening of the SWNTs during DGU sorting caused the lowering of the conductivity as pointed out previously [42], which is also supported by our Raman spectra (Supporting information, Figure S1) and AFM images (Supporting information, Figure S2). Such a lowering of the electrical conductivity is supported by the theoretical simulation as well [43].…”
Section: Preparation Of S-swnt Sheetssupporting
confidence: 53%
See 1 more Smart Citation
“…Slight doping with 0.1 mg mL −1 AgTFSI dramatically increased electrical conductivity to 7.8 S cm −1 , and the reduction of film resistivity down to less than a mega-ohm enabled the reliable measurement of the Seebeck coefficient. The order of the obtained Seebeck coefficient (~ 235 μV K −1 ) corresponds approximately to the theoretical value of slightly doped s-SWNTs [19]. Using identical feedstock films, we examined the doping effect on the thermoelectric transport.…”
Section: Resultsmentioning
confidence: 62%
“…Recent research works have demonstrated that finite-layer nanotubes are promising thermoelectric materials with many advantages [22][23][24] . First, nanotubes are one-dimensional materials, leading to high Seebeck coefficient due to the quantum confinement effect [25][26][27] . Second, the natural network structures with multiple intertube junctions significantly reduce the thermal conductivity, leading to large figureof-merit values 28,29 .…”
Section: Introductionmentioning
confidence: 99%